2022
DOI: 10.1186/s13550-022-00910-1
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter single-photon emission computed tomography-derived radiomics signature for detecting Parkinson’s disease

Abstract: Background We hypothesised that the radiomics signature, which includes texture information of dopamine transporter single-photon emission computed tomography (DAT-SPECT) images for Parkinson’s disease (PD), may assist semi-quantitative indices. Herein, we constructed a radiomics signature using DAT-SPECT-derived radiomics features that effectively discriminated PD from healthy individuals and evaluated its classification performance. Results We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Following the exclusion of 121 duplicate studies, 43 studies were screened based on their titles or abstracts. Ultimately, a total of 28 articles ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Dhinagar et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) were deemed eligible and included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the exclusion of 121 duplicate studies, 43 studies were screened based on their titles or abstracts. Ultimately, a total of 28 articles ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Dhinagar et al, 2021 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) were deemed eligible and included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in this research are shown in Table 1 and Supplementary Table 4 . The original 28 studies were published between 2019 and 2022, with 27 of them from Asia ( Cheng et al, 2019 ; Shinde et al, 2019 ; Wu et al, 2019 ; Xiao et al, 2019 ; Cao et al, 2020 , 2021 ; Liu et al, 2020 ; Pang et al, 2020 , 2022 ; Shu et al, 2020 ; Hu et al, 2021 ; Li et al, 2021 , 2022 ; Ren et al, 2021 ; Shi et al, 2021 , 2022a , 2022b ; Sun et al, 2021 , 2022 ; Tupe-Waghmare et al, 2021 ; Zhang et al, 2021 ; Ben Bashat et al, 2022 ; Guan et al, 2022 ; Kang et al, 2022 ; Kim et al, 2022 ; Shiiba et al, 2022 ; Zhao et al, 2022 ) and one from North America ( Dhinagar et al, 2021 ). The study comprised a total of 6,057 participants, with 3,422 patients diagnosed with PD, 1,983 healthy controls, and 652 cases of APS (476 with MSA and 176 with PSP).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, some researchers have developed algorithms to solve these problems. In this line, Shiiba et al [ 231 ] developed a DAT-SPECT image-derived radiomics signature and reported that their model would be useful for the diagnosis of PD and would have the potential to provide robust diagnostics. In addition, SPECT has been used in the diagnosis of AD due to its potential to provide information on regional cerebral blood flow, which has been postulated as a determinant of this disease.…”
Section: Neuroimaging Techniques In Studying Neuro-vulnerabilitymentioning
confidence: 99%
“…Notably, no model was built here for subtyping the dopaminergic denervation into PD/ atypical-parkinsonisms. Shiiba et al compared DAT-SPECT conventional features and a radiomics signature for the classification of 413 PPMI patients into PD or HC (31). Radiomics signature included features mostly from putamen and pallidum and was up to 96.8% accurate in the discrimination of PD patients.…”
Section: Diagnosis and Early Differentiation From Atypical Parkinsonismsmentioning
confidence: 99%